Bending Collapse of Closed-hat-section Beams. Part II: Theoretical Model Modification and Validation / Hafizan Hashim ... [et al.] - Hashim, Hafizan; Ab. Ghani, Amir Radzi; Wahyu, Kuntijoro (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
This is the second part of the study on the bending collapse of closed-hat-section beams. This part presents an attempt to modify an existing theoretical model to predict the bending collapse mechanism and the bending response of closed-hat-section beams subject to pure bending. Previous Kecman collapse model is the main reference in the present study. According to Kecman, bending collapse of rectangular tubes exhibited so called ‘hinge mechanism’ on the compression flange but no significant plastic deformation was observed on the tensile side of the flange. Similarly when a closed-hat-section is bent inward, the yield line due to tensile has less influence on the overall plastic deformation. A failure mechanism consisting of stationary and rolling pastic hinge lines to produce an analytical solution using limit analysis techniques is proposed. In order to validate the analytical solution, a series of finite element analysis on pure bending of closed-hat-section beams is demonstrated. The resulting moment-rotation characterisitcs are compared with modified Kecman analytical model. Good agreement is achieved through the comparison, and the derived analytical model is therefore validated.